Why do participants enroll in population biobank studies? A systematic literature review. (January 2013) - Nobile, Hélène; Vermeulen, Eric; Thys, Kristof; Bergmann, Manuela M; Borry, Pascal
Therapeutic misconception has been extensively studied and addressed within clinical trials. An equivalent in the genetic research context has been identified as diagnostic misconception. There is not much data on this phenomenon in population-based biobank studies. Since misconceptions may generate undue motives to enroll, the authors aimed at reviewing studies addressing the reasons to participate in biobank studies. The main databases were searched using relevant keywords. Studies were included if peer-reviewed, in English and describing the reasons to enroll was provided by actual and apparently healthy donors. Although the 13 studies retrieved were heterogeneous, a scheme summarizing the main aspects involved in the decision-making process was developed. Expectation of personal benefit through health-related information was found in eight studies. Three of them discussed whether this expectation could be considered a form of therapeutic misconception. The magnitude of this phenomenon is an important ethical concern and ought to be further studied.